MANAGEMENT FISIOTERAPI PADA KASUS POST OP TFCC (TRIANGULAR FIBRO CARTILLAGE COMPLEX) SINISTRA DI KLINIK ARA PHYSIOTHERAPY TANGERANG - Hilda Bramila Ratimaya; Totok Budi Santoso; Abdurrasyid Abdurrasyid (Journal of Innovation Research and Knowledge, 2023)
Introduction: Distal radius fracture is a type of fracture that usually occurs in the wrist. Generally it often occurs due to falling in a state of resting hands and usually occurs in children and the elderly. If a person falls on an outstretched arm, the hand will suddenly stiffen, and then cause the hand to twist and compress the forearm. The type of injury that occurs as a result of this condition depends on the age of the patient. Purpose: of this research is to find out the Physiotherapy Management in Left Left Post Op TFCC (Triangular Fibro Cartilage Complex) Cases. Methods: the patient is given Transcutaneous Electrical Nerve Stimulation, Ultrasound and Wrist Exercise for 4 weeks. Results: the evaluation was carried out using the Numeric Rating Scale, Range Of Motion (ROM), Manual Muscle Testing. Conclusion: Based on the treatment of the left Post Op TFCC (Triangular Fibro Cartilage Complex) case by providing three intervention methods in the form of transcutaneous electrical nerve stimulation, ultrasound and wrsit exercise providing much more progress in overcoming the problems in this case